2012
DOI: 10.1021/pr300557m
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum Schizont Phosphoproteome Reveals Extensive Phosphatidylinositol and cAMP-Protein Kinase A Signaling

Abstract: The asexual blood stages of Plasmodium falciparum cause the most lethal form of human malaria. During growth within an infected red blood cell, parasite multiplication and formation of invasive merozoites is called schizogony. Here, we present a detailed analysis of the phosphoproteome of P. falciparum schizonts revealing 2541 unique phosphorylation sites, including 871 novel sites. Prominent roles for cAMP-dependent protein kinase A- and phosphatidylinositol-signaling were identified following analysis by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(171 citation statements)
references
References 60 publications
12
158
1
Order By: Relevance
“…For any site within six residues of the N-or C terminus of its largest contiguous sequence, the VBA program used the inferred protein sequence to extend the site neighborhood to give a phosphosite-centered 13-mer sequence. Sequences were categorized as basic, acidic, proline-directed, tyrosine, or "other" according to the rules of Huttlin and colleagues (23), well-articulated by Lasonder and colleagues (25). Motifs were determined for each category using Motif-X (http://motif-x.med.harvard.…”
Section: Methodsmentioning
confidence: 99%
“…For any site within six residues of the N-or C terminus of its largest contiguous sequence, the VBA program used the inferred protein sequence to extend the site neighborhood to give a phosphosite-centered 13-mer sequence. Sequences were categorized as basic, acidic, proline-directed, tyrosine, or "other" according to the rules of Huttlin and colleagues (23), well-articulated by Lasonder and colleagues (25). Motifs were determined for each category using Motif-X (http://motif-x.med.harvard.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that physical interactions between proteins can be regulated by phosphorylation (Lasonder et al 2012). To better elucidate virus infection processes regulated by phosphorylation, a protein-protein interaction network (Fig.…”
Section: Protein-protein Interactions Analysismentioning
confidence: 99%
“…To date there have been five mass spectrometry malaria parasite phosphoproteomes published that have established that protein phosphorylation plays a wide regulatory role in malaria, controlling key processes such as metabolism and cell growth, as well as malaria-specific processes such as egress, invasion and cytoadherence [16][17][18][19][20]. The basic work flow for a global phosphoproteome study is as follows:-1) extraction of most of the proteins in the parasite infected cell; 2) digestion of the proteins to small peptides with, for example, trypsin (an enzyme which cuts at lysine or arginine residues); 3) chromatographic fractionation of the peptides to simplify the complexity of the sample; 4) enrichment of phosphopeptides using an enrichment technique such as IMAC (immobilized metal affinity chromatography) or TiO 2 and 5) identification of the peptides and the phosphorylation sites on a mass spectrometer .…”
Section: Defining the Phosphoproteome Of The Malaria Parasitementioning
confidence: 99%
“…Lasonder et al, [17] also identified the phosphoproteome of schizont stage of the parasite where they reported phosphopeptides with a mascot score of at least 15, 1% false discovery rate and 75%…”
Section: Defining the Phosphoproteome Of The Malaria Parasitementioning
confidence: 99%
See 1 more Smart Citation